2014
DOI: 10.1039/c4ce01678e
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia assisted formation of tubular MOP-18 crystals

Abstract: Tubular MOP-18 crystals have been successfully prepared by cooling-induced crystallization from copper hydroxide nanostrands and 5-dodecyloxybenzene-1,3-dicarboxylic acid DMF (N, N-dimethyl-formamide)/ammonia solution. The dependence of the crystal morphologies on the cooling rate is investigated in detail. Slower cooling rate results in larger and longer MOP-18 tubes. Ammonia in DMF solution plays a crucial role in the formation of MOP-18 tubes. It deprotonates the acid ligand to trigger the nucleation of MOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…EG 3 ‐MOPs were readily synthesized by the self‐assembly of copper(II) and 5‐tri(ethylene glycol) monomethyl ether isophthalic acid (TEGME‐IPA) at 80 °C in DMF, which was then precipitated by the addition of diethyl ether. FT‐IR spectra of TEGME‐IPA and EG 3 ‐MOP revealed that the C=O stretching vibration for carboxylic acid of TEGME‐IPA was observed at 1707 cm −1 , which disappeared in EG 3 ‐MOP (Figure S1) . In addition, the O‐C‐O stretching modes of carboxylate were observed at 1640 and 1590 cm −1 by asymmetric vibration and 1450 and 1380 cm −1 by symmetric vibration, indicating the coordination to Cu II by the deprotonation of TEGME‐IPA …”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…EG 3 ‐MOPs were readily synthesized by the self‐assembly of copper(II) and 5‐tri(ethylene glycol) monomethyl ether isophthalic acid (TEGME‐IPA) at 80 °C in DMF, which was then precipitated by the addition of diethyl ether. FT‐IR spectra of TEGME‐IPA and EG 3 ‐MOP revealed that the C=O stretching vibration for carboxylic acid of TEGME‐IPA was observed at 1707 cm −1 , which disappeared in EG 3 ‐MOP (Figure S1) . In addition, the O‐C‐O stretching modes of carboxylate were observed at 1640 and 1590 cm −1 by asymmetric vibration and 1450 and 1380 cm −1 by symmetric vibration, indicating the coordination to Cu II by the deprotonation of TEGME‐IPA …”
Section: Figurementioning
confidence: 97%
“…brationf or carboxylic acid of TEGME-IPAw as observed at 1707 cm À1 ,w hich disappeared in EG 3 -MOP ( Figure S1). [22] In addition, the O-C-O stretching modes of carboxylate were observed at 1640 and 1590 cm À1 by asymmetric vibration and 1450 and 1380cm À1 by symmetric vibration, indicating the coordinationt oCu II by the deprotonation of TEGME-IPA. [23] To clearly determine the structure of EG 3 -MOP,s ingle-crystals suitable for synchrotron X-ray diffraction were obtained by slow diffusion of diethyl ether into aD MF solution of EG 3 -MOPs at 5 8C( Figure S2).…”
mentioning
confidence: 97%